Characterisation of physicochemical properties of different oat cultivars used in noodle processing: effects on quality and β-glucan - Mitra, Sabori (Curtin University, 2015)
Research characterised the physicochemical properties of different oat cultivars used in noodle processing and their effects on noodle quality and β-glucan content. The effect of oat cultivar, season and processing on noodle and β-glucan quality was investigated. This research provided an insight into the quality differences between oat cultivars, effect of season on oat cultivar quality and the oat cultivars most suitable for incorporation into oat-wheat noodles in terms of processing, sensory and nutritional properties.